2011
DOI: 10.2478/v10014-011-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of number of deaths in accidents with the agriculture and forestry tractors among European countries

Abstract: Agricultural and forestry tractors are very often involved in accidents with overturning because of their construction with a high centre of gravity. Such accidents are caused by various factors such as drivers, vehicles, driving conditions, or landscape/terrain. The data related to the number of deaths in accidents with agriculture and forestry tractors was collected from several European countries. The landscapes (or terrain) of the countries for tractor traffic was assessed by the coefficient of the topogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…With respect to the countries in Cluster 2, there are several differences among them regarding economical and topographic conditions. Bernik and Jeroncic (2011) accidents in 22 European countries between 1990 and 1999. According to their analysis, these factors had no significant impacts on the incidence rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the countries in Cluster 2, there are several differences among them regarding economical and topographic conditions. Bernik and Jeroncic (2011) accidents in 22 European countries between 1990 and 1999. According to their analysis, these factors had no significant impacts on the incidence rate.…”
Section: Resultsmentioning
confidence: 99%
“…The results of their study revealed that Sweden had the lowest numbers in this regard. In another study, the number of fatal tractor accidents in the agriculture and forestry sector among EU countries was compared (Bernik and Jeroncic, 2011). Suchomel et al (2013) compared Austria, Slovakia, and the Czechia with regard to the forestry, agriculture, and fishing sectors by considering the fatal accident rates, concluding that Austria had the highest rates.…”
Section: Introductionmentioning
confidence: 99%